Patent Protection in the Shadow of Infringement: Simulation Estimations of Patent Value - Olson Lanjouw, Jean (Review of Economic Studies, 1998)
Empirical estimates of the private value of patent protection are derived for four technology areas—computers, textiles, combustion engines, and pharmaceuticals—using new patent data for West Germany, 1953–1988. Patentees must pay renewal fees to keep their patents in force as well as legal expenses in order to enforce them. A dynamic stochastic discrete choice model of optimal renewal decisions is developed incorporating both learning and depreciation as well as the potential need to prosecute infringement. The evolution of the distribution of returns over the life of a group of patents is calculated for each technology using a minimum distance simulation estimator. Results indicate that the aggregate value of protection generated per year is on the order of 10% of related R&D expenditure.